Application of Set Pair Analysis Model Based on Interval Number in Water Quality Evaluation - Jundong, SI; Mian, LU; Zhijun, WU; Fanxiu, LI (International Journal of Scientific Research and Management (IJSRM), 2019)
Aiming at the problem of losing information when the monitoring value is averaged during the water quality evaluation process, the method of converting the interval number into the contact number is proposed, and the interval number model of the set pair analysis number is established. The model was applied to the Fenhe River for water quality evaluation. The evaluation results were basically consistent with the results of the interval clustering method, and the value of i had no effect on the water quality evaluation results when [0,1]. The model calculation process in this paper is simple and fast, and the evaluation results are feasible and effective, which provides a scientific basis for water environment management.